Management of a rare combination of dental trauma: A case report - Suprabha B; Mogra S (Wolters Kluwer Medknow Publications, 2007)
The occurrence of combined injury of intrusion, avulsion and lateral luxation is rare and the mechanism responsible for this is intriguing. This case report describes such a combined injury and its management. The rationale behind the treatment modalities is discussed.